Spatial analysis for calculating closest distance of operators' location to Base Transceiver Station (BTS) in Banda Aceh city. Issue 1 (March 2020) - Nizamuddin,; Afidh, R P F; Ardiansyah,; Sofyan, H; Anisah, N
Abstract: Base Transceiver Station (BTS) is used to generate auxiliary signal for cellular uses. BTS will support all the activities regarding data exchange such as messaging and web browsing. The spatial data plays important role to support BTS's signal coverage area. The spatial data also can be used for designing of new cellular networks and construction new BTS. This research purpose is to help operator manager find the distance of BTS distribution that will be used to make group of BTS position for the operators. In this research Geographic Information Systems (GIS) has been utilized to analyse the nearest distance and to create group of BTS. Spatial network analyst uses network data path to find out the nearest distance from operators' location to all of BTS in Banda Aceh by using tools closest facility, and to analyse the operators' location grouping based on the mean value BTS distance by using buffer method. The result of this research has calculated the average distance from the operators' location to all BTS is 6.2 Kilometres. Based on the average distance the first team will manage 7 BTS and the second team will manage 14 BTS.